HCG therapy in azoospermic men with lower or borderline testosterone levels and the prognostic value of Y‐deletion analysis in its outcome. (6th October 2021) - Andrabi, Syed Waseem; Saini, Pallavi; Joshi, Meghali; Mehta, Poonam; Makker, Girish Chandra; Mishra, Geetanjali; Rajender, Singh
Abstract: The purpose of this study was to investigate the efficacy of hCG therapy in hypogonadotropic hypogonadic (HH) azoospermic males along with dissecting the prognostic value of Y‐deletion analysis in these patients. Fifty‐eight azoospermic infertile males with diminished testosterone levels (≤400 ng/dl) and hypogonadism symptoms were subjected to human chorionic gonadotropin (hCG) therapy, and Y‐deletion analysis was undertaken. Post‐treatment, 43% (25/58) patients showed improvement in sperm count with 8.6% (5/58) turning severe oligozoospermic, 24.14% (14/58) patients turning oligozoospermic and 10.54% (6/58) turning normozoospermic. Among responders, the mean sperm concentration was 8.47 ± 13.16 million/ml, sperm count was 17.05 ± 26.17 million, sperm motility was 52.59% ± 25.09% and sperm progressive motility was 26.91% ± 20.51%. Seventeen out of 25 (68%) responders and 11/33 (33%) nonresponders showed an improvement in libido post‐therapy. A Y‐deletion was observed in 8% (2/25) responders and in 39.39% (13 out of 33) nonresponders. The Y‐deletions were more often found in nonresponders in comparison with the responders (Fisher's exact probability test, p  = .007, one tailed). We conclude that hCG therapy in hypogonadotropic azoospermic males is effective in improving andrological parameters and sperm production and that Y‐chromosome deletion analysis has prognostic significance in predicting the success of hCG therapy.